Excellent dynamic stability under saturated salt solution for aqueous quantum dots capped by multi-branched ligands. (13th September 2016) - Xu, Jingkun; Xu, Shuhong; Lv, Changgui; Wang, Chunlei; Cui, Yiping
Abstract: Preparing quantum dots (QDs) with strong stability against salts is extremely important in some environments with ultrahigh salts concentration, such as the oil exploitation, wastewater treatment and biological markers. In this paper, we reported a simple new method to prepared highly stable QDs by using multi-branched ligands. Our results suggested that multi-branched ligands-capped QDs have extremely good dynamic stability even in salt-saturated solution. Unlike to traditional dynamic stability theory, which considers the electrostatic repulsion of QDs dominant QD stability, the current work found a new determined factor: the steric hindrance of ligand structure. The high steric hindrance effect of multi-branched ligands can maintain the single dispersity of QDs even at extremely low electrostatic repulsion. As a result, QDs with ultrahigh stability against salts can be realized.